Penerapan Model Konseling Dalam Meningkatkan Motivasi Dan Minat Belajar Siswa/I Di Smp Permata Harapan Batam - Moralman Gulo; Benteng MM Purba; Ronald Sianipar; Elisya Nita Anugrahni; Fran Erikson; Mery Cristina Lumban Gaol; Andre Setiawan; Hertina Mewani simangunsong; Tirina Linda Sari; Romaulina Sinaga; Peronika Kristiani simbolon; Minta Minaria (Sekolah Tinggi Pariwisata Mataram, 2023)
The community service program held at Permata Harapan Middle School aims to increase interest in learning and motivate students to have an enthusiastic spirit in completing their education. One of the efforts to make this happen, the PKM team created a counseling room for students as a place to find solutions to any difficulties they experienced. This counseling activity is a process to provide assistance in order to accompany students to find a way out of each of their problems. The method used in this activity is a qualitative descriptive method which is carried out in three stages. First is preparation, where the team makes observations at the activity site, then compiles what partners need, secondly implementation, this stage the team guides and conducts counseling for students and finally the evaluation stage which measures the extent to which this activity was successful. Through this activity students are motivated and experience an increased interest in learning to complete their education.